Structure-based discovery of novel inhibitors of Mycobacterium tuberculosis CYP121 from Indonesian natural products. (April 2020) - Prasasty, Vivitri Dewi; Cindana, Sandra; Ivan, Fransiskus Xaverius; Zahroh, Hilyatuz; Sinaga, Ernawati
Graphical abstract: Highlights: CYP121 plays an essential role in targeting multidrug-resistant (MDR) and extensively drug-resistant (XDR) TB bacteria. Forty-eight pharmacophore screening were possessed, where sixteen constituents were found as new antituberculosis potential. Medicinal plants, including Rhoeo spathacea and Pluchea indica are great sources to have good antituberculosis activities. Kaempferol (KAE) and benzyl derivative (KAE3) are identified as great CYP121 inhibitors. Abstract: Tuberculosis (TB) continues to be a serious global health threat with the emergence of multidrug-resistant tuberculosis (MDR-TB) and extremely drug-resistant tuberculosis (XDR-TB). There is an urgent need to discover new drugs to deal with the advent of drug-resistant TB variants. This study aims to find new M. tuberculosis CYP121 inhibitors by the screening of Indonesian natural products using the principle of structure-based drug design and discovery. In this work, eight natural compounds isolated from Rhoeo spathacea and Pluchea indica were selected based on their antimycobacterial activity. Derivatives compound were virtually designed from these natural molecules to improve the interaction of ligands with CYP121. Virtual screening of ligands was carried out using AutoDock Vina followed by 50 ns molecular dynamics simulation using YASARA to study the inhibition mechanism of the ligands. Two ligands, i.e., kaempferol (KAE) and its benzyl derivative (KAE3), are identified as the best CYP121 inhibitors based on their binding affinities and adherence to the Lipinski's rule. Results of molecular dynamics simulation indicate that KAE and KAE3 possess a unique inhibitory mechanism against CYP121 that is different from GGJ (control ligand). The control ligand alters the overall dynamics of the receptor, which is indicated by changes in residue flexibility away from CYP121 binding site. Meanwhile, the dynamic changes caused by the binding of KAE and KAE3 are isolated around the binding site of CYP121. These ligands can be developed for further potential biological activities.